MODEL PELAPORAN CORPORATE SOCIAL RESPONSIBILITY TEMA KEMASYARAKATAN, LINGKUNGAN DAN PRINSIP PENGUNGKAPAN PADA PT. ALAM MAHAMERUDI KOTA MALANG - Aniek Murniati (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2013)
This research is to study implementation of corporate social responsibility report (society and environment theme) at PT. Alam Mahameru in Malang and to known disclosure report consistency (full disclosure). This research is descriptive research with data type qualitative, which is described and explains obtained data of PT. Alam Mahameru. Collecting data with some method of like semi interview structure to some employees of PT. Alam Mahameru, observation non participant and documentation in the form of document, soft copy, hard copy and also other media exist in PT. Alam Mahmeru.Result of Research indicate that PT. Alam Mahameru have applied corporate social responsibility society and environment theme as according to rules and regulations of No. 40 Year 2007 ( UUPT) but PT. Alam Mahameru have not consist use CSR report consistency (full disclosure). CSR implementation in PT Alam Mahameru expected the company to have sustainability reporting (SR) who reported social, economic and environmental aspects of a company. This report is beyond the concept or reported separately to the financial statements conformed to the applicable accounting standards.This report is expected to be included in the annual report, so the company is able to reveal the social impact of the company with the principle of full disclosure (full disclosure).